1994
DOI: 10.1111/j.1399-3054.1994.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of elastic and osmotic adjustments to turgor maintenance of woody species.

Abstract: 1994. The relative contribution of elastic and osmotic adjustments to turgor maintenance of woody species. -Physiol. Plant. 90; 408-413.To determine how tissue water relations vary and contribute to turgor maintenance in species from contrasting ecological zones, seedlings of jack pine {Pinus banksiana Lamb.), black .spruce iPicea mariana |Mill) B.S.P.I and flooded gum (Eucalyptus grandis W. Hilt ex Maiden) were subjected to an 8 day drought stress by water withholding with and without prior mild water stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 13 publications
2
24
0
5
Order By: Relevance
“…Furthermore, development of increased leaf water deficits upon discontinuing irrigation may circumstantially be more rapid (or severe) in genotypes having greater amplitude of OA (Meinzer et al, 1990b;DaMatta et al, 1993). These observations imply that OA may not be an effective mechanism of drought tolerance in coffee, as has also been reported for several other woody species (Fan et al, 1994).…”
Section: Water Relationsmentioning
confidence: 79%
“…Furthermore, development of increased leaf water deficits upon discontinuing irrigation may circumstantially be more rapid (or severe) in genotypes having greater amplitude of OA (Meinzer et al, 1990b;DaMatta et al, 1993). These observations imply that OA may not be an effective mechanism of drought tolerance in coffee, as has also been reported for several other woody species (Fan et al, 1994).…”
Section: Water Relationsmentioning
confidence: 79%
“…Los cambios requeridos a nivel de paredes celulares para llevar a cabo el ajuste elástico, que son mencionados por Zwiazek (1991), podrían explicar una respuesta de más largo plazo en el módulo de elasticidad. Si bien el ajuste osmótico y el ajuste elástico no se desarrollan en conjunto, o tienden a asumir uno mayor relevancia sobre el otro (Fan et al 1994), ambos mecanismos requieren de posteriores estudios que aclaren la participación de estos en la regulación de la turgencia en peumo.…”
Section: Discussionunclassified
“…A lower cell wall elasticity would allow leaf water potential to drop rapidly and substantially as soon as the leaves began to loose water [34,38] and a rapid recovery after a decrease in soil water content, which is shown as an efficient mechanism to overcome water stress [14]. It has been suggested that a higher ε max value increases water absorption in a drying soil by increasing the soil-plant water potential gradient [18]; although both lower and higher elasticity have been suggested as promoting turgor maintenance.…”
Section: (A) (B)mentioning
confidence: 99%